Integrated product-process design to suggest appropriate manufacturing technology: a review - Khaleeq uz Zaman, Uzair; Siadat, Ali; Rivette, Mickael; Baqai, Aamer Ahmed; Qiao, Lihong (International journal of advanced manufacturing technology, 2017)
The materials and manufacturing processes are evolving very rapidly subject to today’s high performance, shorter lead times, and high part complexity needs. With over 80,000 materials, various manufacturing technologies (additive and traditional), diverse streams of application (aerospace, motor vehicles, health care, etc.), and high cost incurred due to manufacturability of the part, it has become essential to choose the right compromise of technology resource in early stages of design considering the Design for Manufacturing (DFM)/Design for Additive Manufacturing (DFAM) guidelines. The concerned literature to date focuses on manufacturing technology selection by being either part specific or application specific. As multiple criteria are involved for decision making, this paper provides a thorough review on the following questions: (1) What are the common design criteria used in literature for additive and traditional manufacturing technologies with respect to product-process integration? (2) What is the literature contribution for material and manufacturing process selection strategies with special focus on comparison of additive and traditional manufacturing technologies? The paper attempts to provide as a result a basic generic methodology for resource selection (RS) which will not only take into account all of the areas of application, DFM/DFAM guidelines, and three design criteria (function, cost, and environment), but will also discuss avenues for collaborative product development. A complex industrial case study is also presented to test the proposed methodology.